The primacy of being - Kornecki, Marek (Folia Philosophica, 2003)
The main theses of the present article can be reduced to the presentation of its four principal aims: 1. A discussion of the strategy of choosing a form of being, and the reconstruction of the two fundamental meanings Dasein as: - an exemplary being (being), - a straightforward being here and now (be-ing). 2. The drawing of the reader’s attention to the two different senses of the term “ontological difference.” As a result of this the category “ontic” is occasionally used by Heidegger as an inner category of the fundamental ontology (ontic = existential), or as a category that is external with regard to the fundamental ontology and belongs to the traditional metaphysics (ontic = creaturely). 3. An attempt at a polemic with the Derridean interpretation of the exemplary nature of being. 4. A demonstration of the coherence of Heidegger’s philosophical discourse, and, particularly, of the fact that the analysis of Dasein constitutes a kind of prolegomena to the late thought (from after the “turn”) of the author of Being and Time, that is to the analysis of the truth of being and event (Ereignis).